Systematic Review of Valve Surgery with Continuous Coronary Perfusion on Beating Heart in Patients with Low Left Ventricular Ejection Fraction. (CARDIOLOGY OF UZBEKISTAN, 2025)
Aim. Beating-heart continuous coronary perfusion (BHCCP) is an alternative to cardioplegic arrest in valve surgery, potentially reducing ischemic reperfusion injury, especially in high-risk patients with low left ventricular ejection fraction (LVEF). Materials and methods. A systematic review of prospective and observational studies was conducted, focusing on BHCCP versus cardioplegia in valve surgery, with emphasis on patients with LVEF <35%. Results. Studies (e.g., Matsumoto et al., 2002) showed no significant difference in mortality or major complications, but BHCCP reduced myocardial damage markers (e.g., Troponin I, CK-MB) by 20–40% compared to cardioplegia. Clinical outcomes remained comparable across groups. Conclusion. BHCCP is a safe alternative to cardioplegia, with potential benefits in myocardial protection, though high-quality randomized trials are needed to confirm clinical superiority.